2008
DOI: 10.1163/156855508x363816
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Finishing of Synthetic Fibers for Medical Applications

Abstract: Demand for antimicrobial fabrics has grown significantly in recent years because of public awareness of the potential threat of spreading diseases and there will be an increasing role for medical textiles in the future world market. The number of applications of polymeric materials for medical purposes is growing very fast. Polymers have found applications in such diverse biomedical fields as tissue engineering, implantation of medical devices and artificial organs, prostheses, ophthalmology, dentistry, bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 79 publications
0
14
0
1
Order By: Relevance
“…Main methods employed to overcome this pitfall include grafting a biocidal group onto fiber polymer branches, 46 cross-linking an enzyme group onto fiber polymer branches, 7,8 and adding an antimicrobial agent into spinning dopes as a filler. 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main methods employed to overcome this pitfall include grafting a biocidal group onto fiber polymer branches, 46 cross-linking an enzyme group onto fiber polymer branches, 7,8 and adding an antimicrobial agent into spinning dopes as a filler. 9…”
Section: Introductionmentioning
confidence: 99%
“…Main methods employed to overcome this pitfall include grafting a biocidal group onto fiber polymer branches, [4][5][6] cross-linking an enzyme group onto fiber polymer branches, 7,8 and adding an antimicrobial agent into spinning dopes as a filler. 9 Many commercially available products of antimicrobial fiber are based on synthetic fibers. For instance, Trevira Bioactive ® , an antimicrobial polyester fiber produced by the German fiber company Trevira, integrated an additive providing silver ions to destroy contacted bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the durability was good for polyester-containing fabrics because the interactions possibly occurred between the antimicrobial agent and hydrophobic polyester polymer surfaces. 19,21 Figure 11 shows the relationship between a number of washing cycles on E. coli for different fabric types. It was found that activity against E. coli value decreased with an increase in a number of washing cycles.…”
Section: Uv Protection Propertiesmentioning
confidence: 99%
“…In this sense, increased importance has been given to strategies for silver encapsulation, which allow the optimization of their release levels to ensure antimicrobial activity and reduce the possibility of adverse effects. For this purpose, inert ceramic matrices and zeolites have been used to immobilize silver ions and thermoplastic polymers, such as polyethylene, polypropylene, and polyamide, which retain silver salts or the metal itself …”
Section: Introductionmentioning
confidence: 99%